2022
DOI: 10.3389/fgene.2022.988703
|View full text |Cite
|
Sign up to set email alerts
|

The soldiers needed to be awakened: Tumor-infiltrating immune cells

Abstract: In the tumor microenvironment, tumor-infiltrating immune cells (TIICs) are a key component. Different types of TIICs play distinct roles. CD8+ T cells and natural killer (NK) cells could secrete soluble factors to hinder tumor cell growth, whereas regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) release inhibitory factors to promote tumor growth and progression. In the meantime, a growing body of evidence illustrates that the balance between pro- and anti-tumor responses of TIICs is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 478 publications
0
3
0
Order By: Relevance
“…Different kinds of immune cells have different functions in tumor development. Tregs, 37 Myeloid‐derived suppressor cells (MDSCs), 38 cancer‐associated fibroblasts (CAFs) 39 and M2 macrophages 40 are generally regarded as tumor accelerative cells, while M1 macrophages, NK cells 41 and CD8 + T cells are recognized as antitumor cells. By analyzing three independent ccRCC sequencing data (TCGA‐KIRC, ICGC‐RECA, and ICI‐RCC) using two different algorithms, we find that LY96 is always positively associated with M2 macrophages, which is considered important for generation of inhibitory ccRCC TME 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Different kinds of immune cells have different functions in tumor development. Tregs, 37 Myeloid‐derived suppressor cells (MDSCs), 38 cancer‐associated fibroblasts (CAFs) 39 and M2 macrophages 40 are generally regarded as tumor accelerative cells, while M1 macrophages, NK cells 41 and CD8 + T cells are recognized as antitumor cells. By analyzing three independent ccRCC sequencing data (TCGA‐KIRC, ICGC‐RECA, and ICI‐RCC) using two different algorithms, we find that LY96 is always positively associated with M2 macrophages, which is considered important for generation of inhibitory ccRCC TME 42 .…”
Section: Discussionmentioning
confidence: 99%
“… 7 Similarly, Shimura et al found a correlation between low LMR and MDSC, with the low LMR group having a higher proportion of MDSC than the high LMR group. 26 While MDSC can be divided into mononuclear-MDSC and polymorphic MDSC, mononuclear-MDSC can differentiate into TAM, and polymorphic-MDSC can produce reactive oxygen species, inhibit T-cell function, 27 promote T regulatory cell formation, 28 and promote tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and density of tumor-associated macrophages are correlated with poor prognosis and resistance to GC treatment [ 10 ]. Antigen-specific cytotoxic CD8 + T cells directly kill tumor cells or mediate their apoptosis through the Fas/FasL signaling pathway [ 11 ]. After the initial antigen stimulation is removed, the memory cells shrink and are found in the tissue and lymph nodes.…”
Section: Introductionmentioning
confidence: 99%